Spatial variability of rainfall erosivity in Brazil - Trindade, Ana Luíza Ferreira; Oliveira, Paulo Tarso Sanches de; Anache, Jamil Alexandre Ayach; Wendland, Edson (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to develop a new rainfall erosivity map for Brazil, using rainfall time series longer than 20 years, and to analyze the spatial distribution of erosivity values. Rainfall data from 1,521 rain gauges were applied to 75 regression equations that relate the mean annual precipitation (P) and the rainfall coefficient (Rc) with the rainfall erosivity index (EI30). Rainfall erosivity values for ungauged regions were obtained by interpolation using the ordinary kriging method. The highest indices were observed between November and February. The results are interpolations that show satisfactory performance for estimating the spatial distribution of the mean annual rainfall erosivity and the EI30 during the months of the year. Therefore, those maps can help on soil and water conservation planning, considering the design of those areas and periods of the year that are considered more critical for rainfall erosivity in Brazil.